Keragaman Karakter Komponen Hasil dan Hasil pada Genotipe Kedelai Hitam - Wirnas, Desta; Trikoesoemaningtyas, ,; Sutjahjo, Surjono Hadi; Sopandie, Didy; Rohaeni, Wage Ratna; Marwiyah, Siti; Sumiati, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
The objective of this research was to determine the trait variance in black soybean lines in terms of yield and yield components. The materials used were F8 lines generated from hybridization of two local varieties, i.e. black seeded Ceneng and greenish yellow seeded Godek, and then selected under single seed descent method, except SC-39-1, SC-62-2 and GC-74-7 that were generated through bulk selection method. The results showed that the traits between plant genotypes were significantly different, except number of productive node and number of unfilled pod. Total variance was contributed more by number of filled pod, seed weight per plant and 100 seed weight. Seed weight per plant and 100 seed weight had high heritability with genetic variance and broad-sense heritability which were significantly different from zero. These characters are important for further selection to improve yields of black soybean lines.Keywords: black soybean lines, broad sense heritability, total variance